Cutaneus Horn pada Aurikula - Yolazenia Yolazenia; Harianto Harianto; Elva Rosiana (Jurnal Ilmu Kedokteran, 2022)
A cutaneous horn is a hard cone-shaped protrusion consisting of dense keratin resembling animal horns, which occurs due to abnormalities in the spinous layer of the epidermis, causing excess keratin accumulation. This disease can be found in any body part, especially in regions exposed to a lot of sunlight, such as the ears. Surgical excision is the treatment of choice for this disease. One case was reported in a male patient aged 75 years with a bulge on the left auricle. The patient underwent surgical excision as management and histopathological examination confirmed the diagnosis of the cutaneous horn with mild-moderate squamous epithelial cell dysplasia. Because of the high association with premalignant and malignant conditions, patients should be followed up regularly to prevent a recurrence.